Role of Lipocalin-2 in Amyloid-Beta Oligomer-Induced Mouse Model of Alzheimer's Disease - Heeyoung Kang; Hyun Joo Shin; Hyeong Seok An; Zhen Jin; Jong Youl Lee; Jaewoong Lee; Kyung Eun Kim; Eun Ae Jeong; Kyu Yeong Choi; Catriona McLean; Kun Ho Lee; Soo Kyoung Kim; et al. (MDPI AG, 2021)
Lipocalin-2 (LCN2) is an inflammatory protein with diverse functions in the brain. Although many studies have investigated the mechanism of LCN2 in brain injuries, the effect of LCN2 on amyloid-toxicity-related memory deficits in a mouse model of Alzheimer's disease (AD) has been less studied. We investigated the role of LCN2 in human AD patients using a mouse model of AD. We created an AD mouse model by injecting amyloid-beta oligomer (AβO) into the hippocampus. In this model, animals exhibited impaired learning and memory. We found LCN2 upregulation in the human brain frontal lobe, as well as a positive correlation between white matter ischemic changes and serum LCN2. We also found increased astrocytic LCN2, microglia activation, iron accumulation, and blood-brain barrier disruption in AβO-treated hippocampi. These findings suggest that LCN2 is involved in a variety of amyloid toxicity mechanisms, especially neuroinflammation and oxidative stress.